The second age of computer science : from ALGOL genes to neural nets - Dasgupta, Subrata (Oxford University Press, 2018)
Between the genesis of computer science in the 1960s and the advent of the World Wide Web around 1990, computer science evolved in significant ways. The author has termed this period the "second age of computer science." This book describes its evolution in the form of several interconnected parallel histories.